Socio-Environmental indicators applied to the assessment of water quality in the agricultural sector. A Review. (Revista Sistemas de Producción Agroecológicos, 2025)
The proper use and management of water resources is of vital importance in human activities, including agricultural activities, where the resource must be periodically monitored using applied indicators. The general objective of this study was to identify socio-environmental indicators in the evaluation of water quality. A systematic review of literature related to socio-environmental indicators applied to the evaluation of water quality in the agricultural sector was conducted, including documents published between the years 2011 to 2022. The databases used were Google Scholar, Science Direct, Springer Link, and Scopus. Articles, books, and scientific reports were included. The review was carried out in four stages. The results reflected that there are three approaches applied to the development of socio-environmental indicators associated with the evaluation of water quality in the agricultural sector. Regarding the trend of research distribution, it was evidenced that Asia, Europe, and America presented greater importance in the development of research on socio-environmental indicators. In countries such as China and Thailand, the highest number of studies associated with socio-environmental indicators in the agricultural sector were observed, promoting the production of clean strategies in accordance with water resource management in activities associated with agriculture.
Keywords: socio-enviromental indicators; water quality; agriculture; agricultural conservation